A kind of high entropy alloy nanoparticle and its application and preparation method

By using metal powders such as Fe, Ni, Mn, Nb, Cu and Ag, high-entropy alloy nanoparticles, and through component regulation and photothermal conversion capabilities, the problem of limited biofilm removal ability of existing high-entropy alloys is solved, and the problem of the existing high-entropy alloys is achieved. Efficient and long-term stable biofilm removal effect.

CN119237725BActive Publication Date: 2025-02-25NORTHEASTERN UNIV CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411777690.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-25
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing high-entropy alloys have limited capabilities in removing biofilms and cannot meet higher application needs. The stability of inorganic nanoparticles and the long-term effect of removing biofilms are insufficient.

Method used

High-entropy alloy nanoparticles are prepared by metal powders such as Fe, Ni, Mn, Nb, Cu and Ag. The introduction of Nb elements through component regulation will promote the precipitation of Cu and Ag ions, enhance the removal of biofilm, and further utilize the photothermal conversion ability. Improve performance.

Benefits of technology

The effect of efficient and long-term stable biofilm removal is achieved. Low concentrations of high-entropy alloy nanoparticles can significantly improve the biofilm removal rate and significantly improve the performance under sunlight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237725B_ABST
    Figure CN119237725B_ABST
Patent Text Reader

Abstract

The present invention discloses a high entropy alloy nanoparticle and its application and preparation method, which belongs to the technical field of removing mature biofilm. The raw materials of the high entropy alloy nanoparticle include metal powders Fe, Ni, Mn, Nb, Cu and Ag; wherein the molar ratio of Fe, Ni and Mn is 1:1:1; the molar ratio of Nb to Fe is x, the molar ratio of Cu to Fe is y, the molar ratio of Ag to Fe is z, 1.0≤x≤12.0, 0.5≤y≤1.5, 0.05≤z≤0.25. The high entropy alloy nanoparticles of the present invention further enhance the effect of removing biofilm by regulating the composition, and the high entropy alloy nanoparticles have excellent photothermal conversion ability under sunlight irradiation, so that the biofilm removal performance is more excellent, and a very small amount of high entropy alloy nanoparticles can achieve efficient, long-term and stable removal of biofilm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of removing mature biofilms, and in particular to high entropy alloy nanoparticles and an application and preparation method thereof. Background Art

[0002] Life and health are one of the most concerned topics. Infectious diseases caused by various bacteria, fungi and viruses have seriously affected human health. Biofilms are surface-associated bacterial communities formed by surface-adherent bacteria and their extracellular polymeric substances, which can provide a protective structure for fixed bacteria and threaten the safety of health-related healthcare occupations, food industry and public health. To address this problem, various biofilm removal strategies and materials have been reported, including hydrogels, metals and antibiotics. Nanoparticles (NPs) have shown great potential in reducing bacterial activity, preventing biofilm formation and eradicating established biofilms due to their large surface area, high reactivity and multifunctional design.

[0003] At present, there are many inorganic nanoparticles used as biofilm removal agents, such as nanogold, nanosilver and nanocopper. Among them, nanosilver has attracted great attention and is now widely used in the medical field. Many studies have shown that nanosilver exerts a broad spectrum of biofilm removal properties through a variety of killing mechanisms, including penetrating bacterial cell membranes, destroying DNA, and producing a large amount of reactive oxygen to destroy cell metabolism. Unlike antibiotics, it is less likely to cause bacterial resistance. Therefore, nanosilver has become an antibiotic substitute for multidrug-resistant bacteria. However, single nanosilver is prone to aggregation and oxidation, resulting in the need for large doses to completely eradicate multidrug-resistant bacteria, and large doses of nanosilver can easily cause cell and tissue toxicity. In addition, how to maintain the long-term biofilm removal properties of inorganic nanoparticles is the biggest challenge for this type of material, because inorganic nanoparticles mainly rely on the precipitation of ions to remove biofilms, but this will obviously reduce the stability, corrosion resistance, and antioxidant properties of inorganic nanoparticles.

[0004] High entropy alloys have excellent corrosion resistance, oxidation resistance, stability and other characteristics due to their unique structure and composition, and have become a research hotspot. High entropy alloy nanoparticles with composite 3d transition metal elements can improve their absorption performance in the solar spectrum by enhancing the dd interband transition, and show excellent photothermal conversion ability. Therefore, the development of high entropy alloy nanoparticles to remove biofilm materials can not only ensure their stability, but also achieve efficient removal of biofilms due to their large specific surface area of ​​nanometer size and a large number of active sites. At the same time, the performance of biofilm removal can be further improved by photothermal conversion under solar irradiation. However, the current high entropy alloys have limited ability to remove biofilms and cannot meet higher application requirements. Therefore, it is of great significance to study and develop a new type of high entropy alloy for more efficient removal of biofilms. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a high entropy alloy nanoparticle and its application and preparation method. The high entropy alloy nanoparticle has a large number of reactive sites to achieve long-term stable and efficient biofilm removal performance, and the biofilm removal performance under light is significantly improved.

[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The present invention provides a high entropy alloy nanoparticle, the raw materials of which include metal powders Fe, Ni, Mn, Nb, Cu and Ag;

[0008] Among them, the molar ratio of Fe, Ni and Mn is 1:1:1;

[0009] The molar ratio of Nb to Fe is x, the molar ratio of Cu to Fe is y, and the molar ratio of Ag to Fe is z.

[0010] Preferably, 1.0≤x≤12.0; more preferably, 5.0≤x≤11.0; further preferably, 8.0≤x≤10.0;

[0011] Preferably, 0.5≤y≤1.5; more preferably, 0.7≤y≤1.2; further preferably, 0.8≤y≤1.0;

[0012] Preferably, 0.05≤z≤0.25; more preferably, z is 0.05 or 0.20 or 0.25;

[0013] The present invention introduces Nb elements through composition regulation, thereby more stably fixing Cu and Ag elements in the high entropy system, promoting the precipitation of Cu and Ag ions, and further enhancing the biofilm removal effect. In addition, due to the enhancement of interband absorption, the high entropy alloy nanoparticles have excellent photothermal conversion ability under solar irradiation, making the biofilm removal performance even better.

[0014] In addition, the high entropy alloy nanoparticles do not need to be loaded on any carrier. Due to their unique composition and structure, the high entropy alloy nanoparticles have a large number of reactive active sites to achieve long-term stable and efficient biofilm removal performance.

[0015] In some specific embodiments of the present invention, the high entropy alloy nanoparticles are represented by FeNiMnNb9Cu 0.9 Ag 0.25 or FeNiMnNb 10 Cu 0.8 Ag 0.20 or FeNiMnNb 10 Cu 0.9 Ag0.05 ; Among them, such as FeNiMnNb9Cu 0.9 Ag 0.25 As shown, it indicates that the molar ratio of the raw metal powder of the high entropy alloy nanoparticles is Fe: Ni: Mn = 1: 1: 1, Nb: Fe = 9: 1, Cu: Fe = 0.9: 1, Ag: Fe = 0.25: 1. Preferably, the particle size of the high entropy alloy nanoparticles is 5-200 nm; more preferably 20-150 nm.

[0016] In the preferred embodiment of the present invention, the crystal phase structure of the high entropy alloy nanoparticles is a single solid solution. The single solid solution is a solid solution having only one structure in the crystal phase structure of the high entropy alloy nanoparticles.

[0017] The high entropy alloy nanoparticles of the present invention have the characteristics of high entropy structure, nanometer size, copper and silver ion precipitation, photothermal conversion, etc., and achieve excellent biofilm removal effect through the synergistic effect of multiple effects. In addition, only a very small amount of high entropy alloy nanoparticles is needed to achieve efficient, long-term and stable biofilm removal effect.

[0018] The present invention also provides the use of the above-mentioned high entropy alloy nanoparticles in removing biofilm;

[0019] Preferably, the concentration of the high entropy alloy nanoparticles is 50-100 μg / mL;

[0020] Preferably, the high entropy alloy nanoparticles have a biofilm removal efficiency of 86%-99.98%.

[0021] More preferably, in the present invention, when the concentration of the high entropy alloy nanoparticles is 50 μg / mL, the biofilm removal rate is 86.29% in the absence of light and 97.81% in the presence of light.

[0022] The biofilm removal performance test specifically comprises the following steps:

[0023] At a constant temperature of 30°C and without light, 10*10*10 mm 316 L stainless steel was mixed with 10 6 CFU / mL of Vietnamese Bacillus was co-cultured in 2216E liquid medium for 24-48 h to culture a mature biofilm. Subsequently, the metal block (316L stainless steel) was co-cultured with high-entropy alloy nanoparticles at a concentration of 100 μg / mL for 3 h, and the biofilm removal rate reached more than 98%. -2 Under irradiation, the biofilm removal rate reached more than 99% after 10-60 min of co-culture.

[0024] If the concentration of the high entropy alloy nanoparticles is 50 μg / mL, the biofilm removal rate reaches more than 86% after 3 h of co-culture. -2 Under irradiation, the biofilm removal rate reached more than 98% after 10-60 min of co-culture.

[0025] The above performance tests show that the high entropy alloy nanoparticles of the present invention have excellent light-to-heat conversion capability and excellent biofilm removal performance. Moreover, the above performance can be achieved at low concentrations.

[0026] Preferably, the bacteria or microorganisms in the biofilm are selected from one or more of Staphylococcus aureus, Escherichia coli, Shewanella, Pseudomonas aeruginosa, and Bacillus vietnam.

[0027] In some specific embodiments of the present invention, Bacillus vietnamese is used.

[0028] The present invention also provides a method for preparing the above-mentioned high entropy alloy nanoparticles, comprising the following steps:

[0029] (1) Mixing metal raw material powder according to a certain ratio and pressing it into a shape to obtain a metal sheet;

[0030] (2) In a mixed atmosphere of protective gas and reaction gas, a DC arc plasma method is used to evaporate the metal sheet and crack the reaction gas, and the high entropy alloy nanoparticles are obtained through cooling and passivation treatment.

[0031] Preferably, the reaction gas is selected from hydrogen or methane;

[0032] Preferably, the protective gas is selected from one or more of helium, neon and argon.

[0033] Preferably, the volume ratio of the reaction gas to the protective gas is (2-10):1, more preferably (2-6):1. In some specific embodiments of the present invention, it is specifically 2:1, 4:1 or 5:1.

[0034] The DC plasma arc furnace method specifically comprises the following steps:

[0035] The metal sheet was placed in a DC arc plasma discharge device as an anode, and a tungsten electrode was used as a cathode. The vacuum was evacuated to 5×10 -3 Pa, hydrogen and protective gas are filled in, the volume of hydrogen is 2-10 times that of protective gas, and the total gas pressure is maintained at 1.0×10 5 -1.0×10 5Pa, ignite the arc, control the current and voltage to 100-300 A and 20-30 V respectively, evaporate the metal sheet, discharge reaction for 5-30 min, and at the same time fill in the condensate and stand for passivation for more than 6 h to obtain the high entropy alloy nanoparticles.

[0036] In the above preparation method, the metal raw material powder is mixed according to the ratio and the weighed amount is preferably 10-100 g.

[0037] The purity of the metal raw material powder is above 99%, and the particle size is 10-400 μm.

[0038] The pressure used in the compression molding is preferably 10-30 MPa.

[0039] The diameter of the metal sheet is preferably 8-20 mm.

[0040] The preparation method is simple, has a high conversion rate, has abundant reaction raw materials, has low equipment cost, and is easy for large-scale industrial production.

[0041] Compared with the prior art, the raw materials of the high entropy alloy nanoparticles provided by the present invention include metal powders Fe, Ni, Mn, Nb, Cu and Ag; wherein the molar ratio of Fe, Ni and Mn is 1:1:1; the molar ratio of Nb to Fe is x, the molar ratio of Cu to Fe is y, the molar ratio of Ag to Fe is z, 1.0≤x≤12.0, 0.5≤y≤1.5, 0.05≤z≤0.25. The high entropy alloy nanoparticles of the present invention further enhance the effect of removing biofilm by regulating the composition, and the high entropy alloy nanoparticles have excellent photothermal conversion ability under solar irradiation, so that the biofilm removal performance is more excellent, and a very small amount of high entropy alloy nanoparticles can achieve efficient, long-term and stable removal of biofilm. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 X-ray diffraction (XRD) pattern of the high entropy alloy nanoparticles prepared in Example 1;

[0043] Figure 2 The transmission electron microscope (TEM) image of the high entropy alloy nanoparticles prepared in Example 1;

[0044] Figure 3 TEM-EDS element distribution diagram of the high entropy alloy nanoparticles prepared in Example 1;

[0045] Figure 4 The ultraviolet-visible-near-infrared absorption spectrum of the high-entropy alloy nanoparticles prepared in Example 1;

[0046] Figure 5This is a temperature variation diagram of the high entropy alloy nanoparticles prepared in Example 1 under irradiation of one standard sun;

[0047] Figure 6 Figure (1) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles, Figure (3) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours using the high entropy alloy nanoparticles prepared in Example 1, Figure (2) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles and irradiated with 1 standard sunlight for 30 minutes, and Figure (4) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours using the high entropy alloy nanoparticles prepared in Example 1 and irradiated with 1 standard sunlight for 30 minutes;

[0048] Figure 7 Figure (1) is a live / dead staining diagram of biofilm bacteria after being kept at 30°C for 24 hours without the application of nanoparticles, Figure (3) is a live / dead staining diagram of biofilm bacteria after being kept at 30°C for 24 hours with the high entropy alloy nanoparticles prepared in Example 1, Figure (2) is a live / dead staining diagram of biofilm bacteria after being kept at 30°C for 24 hours without the application of nanoparticles and irradiated with 1 standard sunlight for 30 minutes, Figure (4) is a live / dead staining diagram of biofilm bacteria after being kept at 30°C for 24 hours with the high entropy alloy nanoparticles prepared in Example 1 and irradiated with 1 standard sunlight for 30 minutes;

[0049] Figure 8 Figure (1) is a scanning electron micrograph of a complete biofilm at a constant temperature of 30°C for 24 hours, and Figure (2) is a scanning electron micrograph of the biofilm removal performance of the high entropy alloy nanoparticles prepared in Example 1 after being kept at a constant temperature of 30°C for 24 hours and irradiated with 1 standard sunlight for 30 minutes;

[0050] Fig. 9 X-ray diffraction (XRD) pattern of high entropy alloy nanoparticles prepared in Comparative Example 1;

[0051] Fig.10 This is a particle size distribution diagram of high entropy alloy nanoparticles prepared in Comparative Example 1;

[0052] Fig.11 TEM-EDS element distribution diagram of high entropy alloy nanoparticles prepared in Comparative Example 1;

[0053] Fig.12 This is a temperature variation diagram of the high entropy alloy nanoparticles prepared in Comparative Example 1 under irradiation of 1 standard sun light;

[0054] Fig.13Figure (1) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles, Figure (3) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours using the nanoparticles prepared in Comparative Example 1, Figure (2) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles and irradiated with 1 standard sunlight for 30 minutes, and Figure (4) is a plate graph of the experimental results of the number of biofilm colonies after being kept at a constant temperature of 30°C for 24 hours using the nanoparticles prepared in Comparative Example 1 and irradiated with 1 standard sunlight for 30 minutes;

[0055] Fig.14 Figure (1) is a live / dead staining diagram of biofilm bacteria after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles, Figure (3) is a live / dead staining diagram of biofilm bacteria after being kept at a constant temperature of 30°C for 24 hours using the nanoparticles prepared in Comparative Example 1, Figure (2) is a live / dead staining diagram of biofilm bacteria after being kept at a constant temperature of 30°C for 24 hours without the application of nanoparticles and irradiated with 1 standard sunlight for 30 minutes, and Figure (4) is a live / dead staining diagram of biofilm bacteria after being kept at a constant temperature of 30°C for 24 hours using the nanoparticles prepared in Comparative Example 1 and irradiated with 1 standard sunlight for 30 minutes;

[0056] Fig.15 Figure (1) is a scanning electron micrograph of a complete biofilm at a constant temperature of 30°C for 24 hours, and Figure (2) is a scanning electron micrograph of the biofilm removal performance of the nanoparticles prepared in Comparative Example 1 after being kept at a constant temperature of 30°C for 24 hours and irradiated with 1 standard sunlight for 30 minutes. DETAILED DESCRIPTION

[0057] In order to further illustrate the present invention, the high entropy alloy nanoparticles provided by the present invention and their applications and preparation methods are described in detail below in conjunction with embodiments.

[0058] Example 1

[0059] (I) A method for preparing high entropy alloy nanoparticles, the specific implementation steps are as follows:

[0060] Step 1: Weigh metal powder with a mass percentage of 99% and a particle size of 100 μm according to the composition of FeNiMnNb9Cu 0.9 Ag 0.25 Prepare 8g. After uniform mixing, use a tablet press to press into a metal sheet with a diameter of 8mm at 15MPa;

[0061] Step 2: Place the metal sheet in a DC arc plasma discharge device as the anode, and the tungsten electrode as the cathode, and evacuate to 1.0×10 -2 Pa, filled with hydrogen and argon, the volume of hydrogen is twice that of argon, and the total gas pressure is maintained at 1.0×10 4Pa, ignite the arc, control the current and voltage at 150A and 20V respectively, evaporate the metal sheet, discharge reaction for 15min, and at the same time fill in condensed water and stand for passivation for 8h to obtain the high entropy alloy nanoparticles.

[0062] 2. Results

[0063] The characterization results are as follows Figures 1 to 5 As shown, Figure 1 XRD analysis shows that it is a simple solid solution structure; Figure 2 TEM analysis shows that the particle size is about 20-150nm. Figure 3 The TEM-EDS element distribution map shows that the elements are uniformly miscible; Figure 4 The UV-visible near-infrared absorption spectrum analysis shows that its average absorption rate in the entire solar spectrum (250-2500nm) is about 96%, where the substrate diagram represents the wavelength distribution of natural light. Figure 4 This indicates that the material has extremely high light absorption and a full spectrum response range. Figure 5 It shows that the high entropy alloy nanoparticles are placed in a standard sunlight (1kW m -2 ) irradiation, the surface temperature of the material changes within 10 minutes. The results show that the high entropy alloy nanoparticles can quickly rise to above 80°C within 50 seconds, and under the irradiation of one sun, its maximum temperature reaches 85.9°C. After the light is removed for 300 seconds, the surface temperature of the material can quickly cool to room temperature within 40 seconds, showing an outstanding light-to-heat conversion ability.

[0064] 3. Biofilm removal performance test

[0065] (1) Preparation of 2216E liquid culture medium

[0066] Dissolve 2216E complete nutrient medium in ultrapure water, sterilize at 121℃ for 30min, and set aside. The composition of 2216E complete nutrient medium is: 19.45g / L NaCl, 5.98g / L MgCl2, 3.24g / L Na2SO4, 1.8g / LCaCl2, 0.55g / L KCl, 0.16g / L Na2CO3, 0.08g / L KBr, 0.034g / L SrCl2, 0.08g / L SrBr2, 0.022g / L H3BO3, 0.004g / L NaSiO3, 0.0024g / L NaF, 0.0016g / L NH4NO3, 0.008g / L NaH2PO4, 5.0g / L peptone, 1.0g / L yeast extract, 0.1g / L ferric citrate.

[0067] (2) Preparation of 2216E solid culture medium

[0068] Dissolve 2216E complete nutrient medium in ultrapure water in the same manner as in step (1), add 20 g / L agar powder, dissolve by ultrasonication, and sterilize at 121°C under high temperature and high pressure for 20 min. After sterilization, take out the medium, pour it into a sterile culture dish, cool and solidify at room temperature, and set aside.

[0069] (3) Preparation of PBS buffer

[0070] Add 1 L of ultrapure water to a volumetric flask, weigh 10.9 g of PBS buffer, dissolve it in 1 L of ultrapure water by heating, and dispense it, sterilize it at 121°C and high temperature and high pressure for 20 min, and set aside.

[0071] (4) Preparation of bacterial suspension

[0072] After the inoculation loop was placed on an alcohol lamp for burning and sterilization, a single colony was picked from the bacterial solid plate. The bacterial species was the common Vietnamese Bacillus. The colony was added to 50 mL of the 2216E liquid culture medium prepared in step (1), and then placed in a shaker at 30°C and 160 rpm for overnight culture. The bacterial solution after overnight culture was taken and the OD (optical density) value of the bacteria was measured using an ultraviolet spectrophotometer. The sterile culture medium was used as a blank control, and the OD value of the bacteria was made between 0.2 and 0.4 by dilution.

[0073] (5) Biofilm removal experiment

[0074] The plate colony counting method was used to evaluate the biofilm removal performance. 10*10*10mm 316L stainless steel was polished with 200 mesh, 500 mesh, and 1000 mesh sandpaper, and then 10 mL of the 2216E liquid culture medium prepared in step (1) was taken and the stainless steel block was added to the culture medium. Then, the mixed solution was inoculated with a concentration of 10 6 CFU / mL of the bacterial suspension prepared in step (4), after culturing for 24 hours, the steel block was removed and a mixture of high entropy alloy nanoparticles with a concentration of 100 μg / mL added to the culture medium was added. One group of samples was placed in a constant temperature incubator at 30°C and cultured for 30 minutes without light. Another group of samples was prepared with the same parameters and placed in a standard sunlight (1kW m -2 ) for 30 min.

[0075] The two groups of samples in step (5) were taken out for plate colony counting. The samples were serially diluted 10 times using the sterile PBS buffer prepared in step (3). 4Use a pipette to draw 100 μL of the diluted sample solution and evenly apply it on the 2216E solid culture medium plate prepared in step (2), and then place the plate in a 30°C constant temperature incubator without light for 24 hours. Finally, take out the plate and count it to calculate the number of live bacteria before and after treatment.

[0076] Number of viable bacteria = average number of colonies in three replicates of the same dilution × dilution factor × 10

[0077] Biofilm removal rate (%) = (number of live bacteria before treatment - number of live bacteria after biofilm removal) / number of live bacteria before biofilm removal × 100%

[0078] The results of biofilm removal are shown in Table 1. Figure 6 , Figure 7 and Figure 8 The experimental results of the corresponding bacteria show that the high entropy alloy nanoparticles of the present invention have excellent biofilm removal effect. Figure 6 Indicates the number of biofilms before and after the application of nanoparticles, and calculates the efficiency of removing biofilms through the number of biofilms. Experimental data show that the removal rate of biofilms (also known as biofilms) after co-culture with the high entropy alloy nanoparticles of the present invention is 99.95%, and the removal rate after illumination is 99.98%; Figure 7 The figure shows the morphology of the biofilm under a fluorescence confocal microscope after live-dead staining, which shows that the removal effect of the biofilm after being treated with the high-entropy alloy nanoparticles of the present invention is significant, and the removal effect is more significant after being irradiated with light; Figure 8 (1) Figure 1 shows the microscopic morphology of the biofilm under a field emission microscope. The results show that the bacteria remain intact and completely adhere to the metal surface. Figure 8 (2) The figure shows that the biofilm begins to fall off after being treated with the high entropy alloy nanoparticles, and the integrity of the bacteria is destroyed, with cracks and depressions occurring, indicating that the biofilm has been removed and the bacteria have died.

[0079] Example 2

[0080] (I) A method for preparing high entropy alloy nanoparticles, the specific implementation steps are as follows:

[0081] Step 1: Weigh metal powder with a mass percentage of 99.5% and a particle size of 1500 μm according to the composition of FeNiMnNb 10 Cu 0.8 Ag 0.20 Prepare 25 g. After uniform mixing, use a tablet press to press into a metal sheet with a diameter of 25 mm at 18 MPa.

[0082] Step 2: Place the metal sheet in a DC arc plasma discharge device as the anode, and the tungsten electrode as the cathode, and evacuate to 0.5×10 -2 Pa, filled with hydrogen and argon, the volume of hydrogen is 5 times that of argon, and the total gas pressure is maintained at 0.5×10 5 Pa, ignite the arc, control the current and voltage at 180A and 24V respectively, evaporate the metal sheet, discharge reaction for 25min, and at the same time fill in condensed water and stand for passivation for 7h to obtain the high entropy alloy nanoparticles.

[0083] (II) Biofilm removal performance test

[0084] The samples were tested for biofilm removal performance. The test parameters and conditions were the same as those in Example 1, except that high-entropy alloy nanoparticles at a concentration of 50 μg / mL were added to the liquid culture medium in step (5). Another group of samples were prepared with the same parameters and placed in a standard sunlight (1 kW m -2 ) for 40 min. The biofilm removal performance results are shown in Table 1.

[0085] Example 3

[0086] (I) A method for preparing high entropy alloy nanoparticles, the specific implementation steps are as follows:

[0087] Step 1: Weigh metal powder with a mass percentage of 99.8% and a particle size of 100 μm according to the composition of FeNiMnNb 10 Cu 0.9 Ag 0.05 Prepare 50 g of the mixture. After uniform mixing, use a tablet press to press the mixture at 15 MPa into a metal sheet with a diameter of 20 mm.

[0088] Step 2: Place the metal sheet in a DC arc plasma discharge device as the anode, and the tungsten electrode as the cathode, and evacuate to 0.5×10 -2 Pa, filled with hydrogen and nitrogen, the volume of hydrogen is 4 times that of nitrogen, and the total pressure is maintained at 2.0×10 5 Pa, ignite the arc, control the current and voltage at 250A and 23V respectively, evaporate the metal sheet, discharge reaction for 20min, and at the same time fill in condensed water and stand for passivation for 7h to obtain the high entropy alloy nanoparticles.

[0089] (II) Biofilm removal performance test

[0090] The biofilm removal performance test was performed on the samples. The test parameters and conditions were the same as those in Example 2. The biofilm removal results are shown in Table 1.

[0091] Comparative Example 1

[0092] (I) A method for preparing high entropy alloy nanoparticles, the specific implementation steps are as follows:

[0093] Step 1: Weigh metal powder with a mass percentage of 99.5% and a particle size of 50 μm according to the composition of FeNiMnNb 12 20 g of Cu1 was prepared and mixed uniformly, and then pressed into a metal sheet with a diameter of 15 mm at 18 MPa using a tablet press.

[0094] Step 2: Place the metal sheet in a DC arc plasma discharge device as the anode, and the tungsten electrode as the cathode, and evacuate to 0.8×10 -2 Pa, filled with hydrogen and argon, the volume of hydrogen is twice that of argon, and the total gas pressure is maintained at 1.0×10 4 Pa, ignite the arc, control the current and voltage at 200A and 24V respectively, evaporate the metal sheet, discharge reaction for 8min, fill with condensed water and let stand for passivation for 12h to obtain high entropy alloy nanoparticles.

[0095] 2. Characterization results

[0096] The characterization results are as follows Figures 9 to 12 As shown, Fig. 9 XRD analysis shows that the high entropy alloy nanoparticles prepared in Comparative Example 1 are a simple solid solution structure; Fig.10 The particle size distribution analysis shows that the particle size is about 41nm. Fig.11 The TEM-EDS element distribution map shows that the elements are uniformly miscible; Fig.12 It shows that when placed under a standard sunlight, its stable temperature is about 87.6℃.

[0097] 3. Biofilm removal performance test

[0098] The samples were tested for biofilm removal performance. The test parameters and conditions were the same as those in Example 1. The biofilm removal results are shown in Table 1.

[0099] Biofilm removal results Figures 13 to 15 shown.

[0100] Comparative Example 2

[0101] (I) A method for preparing high entropy alloy nanoparticles, the specific implementation steps are as follows:

[0102] Step 1: Weigh metal powder with a mass percentage of 99.8% and a particle size of 100 μm according to the composition of FeNiMnTi 12 Cu1Ag 0.25 Prepare 16 g. After uniform mixing, use a tablet press to press into a metal sheet with a diameter of 10 mm at 22 MPa.

[0103] Step 2: Place the metal sheet in a DC arc plasma discharge device as the anode, and the tungsten electrode as the cathode, and evacuate to 1×10 -2 Pa, filled with hydrogen and argon, the volume of hydrogen is 2.5 times that of argon, and the total gas pressure is maintained at 2.0×10 4 Pa, ignite the arc, control the current and voltage at 220A and 25V respectively, evaporate the metal sheet, discharge reaction for 6min, fill with condensed water and let stand for passivation for 9h to obtain high entropy alloy nanoparticles.

[0104] (II) Biofilm removal performance test

[0105] The samples were tested for biofilm removal performance. The test parameters and conditions were the same as those in Example 1. The biofilm removal results are shown in Table 1.

[0106] Table 1 Test results of biofilm removal performance of nanoparticles in Examples 1-3 and Comparative Examples 1-2

[0107]

[0108] In Table 1, the 50 μg / mL high-entropy alloy nanoalloy used in the biofilm removal performance test of Example 2 has a concentration lower than that of Examples 1, 3 and Comparative Examples 1-2, but it still achieves good biofilm removal performance under no light conditions, and when the conditions are changed to light, its biofilm removal performance is significantly improved compared with the no light conditions, which indicates that the high-entropy alloy nanoalloy described in the present invention has excellent biofilm removal performance even at a low concentration.

[0109] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A high entropy alloy nanoparticle, characterized in that: Its raw materials include metal powders Fe, Ni, Mn, Nb, Cu and Ag; Wherein, the molar ratio of Fe, Ni and Mn is 1:1:1; The molar ratio of Nb to Fe is x, the molar ratio of Cu to Fe is y, the molar ratio of Ag to Fe is z, 1.0≤x≤12.0, 0.5≤y≤1.5, 0.05≤z≤0.25; The crystal phase structure of the high entropy alloy nanoparticles is a single solid solution.

2. The high entropy alloy nanoparticles according to claim 1, characterized in that: The particle size of the high entropy alloy nanoparticles is 5-200 nm.

3. Use of the high entropy alloy nanoparticles according to claim 1 or 2 in removing biofilm.

4. The use according to claim 3, characterized in that The concentration of the high entropy alloy nanoparticles is 50-100 μg / mL; The high entropy alloy nanoparticles have an efficiency of 86%-99.98% in removing biofilm.

5. The use according to claim 3, characterized in that: When the concentration of the high entropy alloy nanoparticles is 50 μg / mL, the biofilm removal rate is 86.29% under no light, and the biofilm removal rate is 97.81% under light.

6. The use according to claim 3, characterized in that: The bacteria or microorganisms in the biofilm are selected from one or more of Staphylococcus aureus, Escherichia coli, Shewanella, Pseudomonas aeruginosa, and Bacillus vietnam.

7. The method for preparing high entropy alloy nanoparticles according to claim 1 or 2, characterized in that: The following steps are involved: (1) Mixing metal raw material powder according to a certain ratio and pressing it into a shape to obtain a metal sheet; (2) In a mixed atmosphere of protective gas and reaction gas, a DC arc plasma method is used to evaporate the metal sheet and crack the reaction gas, and the high entropy alloy nanoparticles are obtained through cooling and passivation treatment.

8. The preparation method according to claim 7, characterized in that: The reaction gas is selected from hydrogen or methane; The protective gas is selected from one or more of helium, neon and argon.

9. The preparation method according to claim 8, characterized in that: The volume ratio of the reaction gas to the protective gas is (2-10):1.

Citation Information

Patent Citations

  • Efficient antibacterial high-entropy alloy nanoparticles as well as preparation method and application thereof

    CN115958192A

  • Multiphasic crystalline nanoparticles and methods of producing thereof

    WO2023113699A2